2005
DOI: 10.1002/ijc.20807
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyltransferase inhibitor SCH‐66336 downregulates secretion of matrix proteinases and inhibits carcinoma cell migration

Abstract: The ras oncogenes are among those most frequently found in human cancers. Blocking Ras farnesylation is a promising strategy for arresting cancer growth. Ras activates several signaling pathways with key roles in cellular proliferation, invasion, metastasis and angiogenesis. Furthermore, proteolytic activities of matrix proteinases such as urokinase-type plasminogen activator (uPA) and matrix metalloproteinases (MMPs) are regulated by Ras isoforms. Thus, we investigated the effects of SCH-66336, a farnesyltran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
(58 reference statements)
2
13
1
Order By: Relevance
“…Our experiments on cells lacking lamin A strongly suggest that some of the beneficial effects of FTI treatment are caused by targeting farnesylated proteins other than lamin A/progerin. Previous reports demonstrate an inhibitory effect of FTI on cell proliferation and migration at high doses (Kouchi et al, 1999;Kusama et al, 2003Kusama et al, , 2006Desrosiers et al, 2005). Our data, using lower doses of FTI, support the inhibitory effect of FTI on proliferation.…”
Section: Discussionsupporting
confidence: 87%
“…Our experiments on cells lacking lamin A strongly suggest that some of the beneficial effects of FTI treatment are caused by targeting farnesylated proteins other than lamin A/progerin. Previous reports demonstrate an inhibitory effect of FTI on cell proliferation and migration at high doses (Kouchi et al, 1999;Kusama et al, 2003Kusama et al, , 2006Desrosiers et al, 2005). Our data, using lower doses of FTI, support the inhibitory effect of FTI on proliferation.…”
Section: Discussionsupporting
confidence: 87%
“…MMPs, such as MMP-2 and MMP-9, display strong activity in tumor cells transformed by Ras [27][28][29]. Contrary to our results, inhibition of Ras by a farnesyltransferase inhibitor reduced levels of secreted MMP-2 and MMP-9 in prostate cancer cells [30]. We observed that FTS together with PDGF and TGFb induced processing of MMP-2 to an active form of approximately 43 kDa.…”
Section: Discussioncontrasting
confidence: 86%
“…Currently, metastatic prostate cancer is incurable and ultimately claims the life of patients (6 -10). An important factor in the relative seriousness of prostate cancer is the invasiveness of the constituent tumor cells causing metastasis (7,11,12). The invasive nature of tumor cells is crucial for cancer metastasis (13,14).…”
mentioning
confidence: 99%